Unique Action of Interleukin-18 on T Cells and Other Immune Cells - Nakanishi, Kenji (Frontiers in Immunology, 2018)
Interleukin (IL)-18 was originally discovered as a factor that enhances interferon (IFN)-g production by anti-CD3-stimulated Th1 cells, particularly in association with IL-12. IL-12 is a cytokine that induces development of Th1 cells. IL-18 cannot induce Th1 cell development, but has the capacity to activate established Th1 cells to produce IFN-g in the presence of IL-12. Thus, IL-18 is regarded as a proinflammatory cytokine that facilitates type 1 responses. However, in the absence of IL-12 but presence of IL-2, IL-18 stimulates NK cells, NKT cells, and even established Th1 cells to produce IL-3, IL-9, and IL-13. Thus, IL-18 also facilitates type 2 responses. This unique function of IL-18 contributes to infection-associated allergic diseases. Together with IL-3, IL-18 stimulates mast cells and basophils to produce IL-4, IL-13, and chemical mediators such as histamine. Thus, IL-18 also induces innate-type allergic inflammation. IL-18 belongs to the IL-1 family of cytokines, which share similar molecular structures, receptors structures, and signal transduction pathways. Nevertheless, IL-18 shows a unique function by binding to a specific receptor expressed on distinct types of cells. In this review article, I will focus on the unique features of IL-18 in lymphocytes, basophils, and mast cells, particularly in comparison with IL-33.